A meta‐analysis of the state and local government borrowing costs. - Gerrish, Ed; Ivonchyk, Mikhail; Charles, Cleopatra; Greer, Robert A.; Moldogaziev, Temirlan T. (Public Administration Review)
State and local governments seek to save money through fiscal efficiency. One such mechanism widely studied in the literature is through the choice for financial underwriting of debt. The extant literature generally suggests that state and local governments can lower borrowing costs through a competitive method of sale. In a meta‐analysis of 418 effects from 97 studies, we find that competitive sales do enjoy a statistically significant reduction in borrowing costs However, these effects are moderated when using key control variables, the use of more recent data, as well as due to measurement and methodological choices. Consequently, despite a large number of studies in this area, more research specific to small borrowers, new and understudied contexts, or those using sophisticated selection and causal methods is needed to understand whether the practical preference for competitive sales should persist.